Achieving Electrical Conductive Tracks by Laser Treatment of non‐Conductive Polypropylene/Polycarbonate Blends Filled with MWCNTs. Issue 7 (26th February 2014) - Liebscher, Marco; Krause, Beate; Pötschke, Petra; Barz, Andrea; Bliedtner, Jens; Möhwald, Michael; Letzsch, Alexander
<x xml:space="preserve">Abstract</x> Electrical non‐conductive polymer blends consisting of a polypropylene (PP) matrix and dispersed particles of polycarbonate (PC) were melt compounded with 3 wt.% multiwalled carbon nanotubes (MWCNTs) loading and processed into plates by injection molding. The morphological analysis confirmed the selective localization of the MWCNTs in the PC component. By local irradiation with a CO2 laser beam, depending on the laser conditions, conductive tracks with dimensions of about 2 mm width, 80 to 370 μm depth and line resistances as low as 1.5 kΩ · cm−1 were created on the surface of the non‐conductive plates. The factors affecting the line resistance are the PC content, the laser speed and laser power, as well as laser direction with respect to the melt flow direction. After the irradiation an enrichment of MWCNTs in the laser lines was detected indicating that conductive paths were generated by percolation of nanotubes selectively within these lines in otherwise non‐conductive plates.<inline-graphic xlink:href="ark:/27927/pghqpm6nww" content-type="mame201300377-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />